2014
DOI: 10.1097/pap.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Selected Case From the Arkadi M. Rywlin International Pathology Slide Series

Abstract: Herein, we report a 26-year-old patient with lymphangiomatosis of the spleen associated with multiple lymphatic and venous malformations. This patient underwent excision of a large lymphatic malformation of the left abdominal wall during childhood. A venous malformation of her left lower limb was excised during adolescence. Additional lymphatic malformations were found in the soft tissue of her left thigh at the age of 20. During hospitalization for a huge vulvar hemangioma at the age of 26, she was incidental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Lymphangiomatosis affects somatic soft tissues in the neck, axilla, mediastinum, retroperitoneum, and extremities, [ 1 , 8 , 9 ] and it predominantly affects the neck (75%) and axilla (20%) in a case series involving children. [ 8 ] The lymphangiomatous process may diffusely involve multiple organ systems when the term “systemic” lymphangiomatosis is applied, [ 1 , 2 , 4 ] and it may be confined to a solitary organ, such as the liver, [ 9 ] spleen, [ 10 ] and kidney. [ 11 ] In the latter condition, lymphangiomatosis is called the “isolated” form.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lymphangiomatosis affects somatic soft tissues in the neck, axilla, mediastinum, retroperitoneum, and extremities, [ 1 , 8 , 9 ] and it predominantly affects the neck (75%) and axilla (20%) in a case series involving children. [ 8 ] The lymphangiomatous process may diffusely involve multiple organ systems when the term “systemic” lymphangiomatosis is applied, [ 1 , 2 , 4 ] and it may be confined to a solitary organ, such as the liver, [ 9 ] spleen, [ 10 ] and kidney. [ 11 ] In the latter condition, lymphangiomatosis is called the “isolated” form.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] In the latter condition, lymphangiomatosis is called the “isolated” form. [ 4 ] It mainly occurs in infants and children and seldom affects patients older than 20 years. [ 12 ] The disease in children is often systemic, while it is mostly isolated in adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a previous study reported that GnRHa therapy following surgery in LPD may prevent the recurrence of new lesions (12). Evidence of long-term efficacy of postoperative treatment in intravenous leiomyomatosis is lacking, and further investigation is required.…”
Section: Discussionmentioning
confidence: 99%